Political Intervention in the Independence of the Constitutional Court in Indonesia - Ahmad Farihy; M. Gymnastiar A.P; Lutfil Ansori (Program Studi Hukum Tata Negara, 2025)
The Constitutional Court of Indonesia was established to safeguard constitutional supremacy and the system of checks and balances; however, its independence has increasingly been challenged by political intervention. This study examines how political interests influence the independence of the Constitutional Court through the mechanisms of judicial selection and dismissal, and how these mechanisms create structural opportunities for political intervention. Employing a normative juridical method, the research analyzes primary legal materials, including constitutional provisions, statutory regulations, and Constitutional Court decisions, supported by secondary sources such as scholarly literature and official legislative records. A focused case study on the replacement of a constitutional judge by the House of Representatives following Constitutional Court Decision Number 96/PUU-XVIII/2020 is used to illustrate these dynamics. The findings demonstrate that the involvement of political institutions in judicial recruitment and removal has systematically weakened judicial independence and undermined security of tenure. This study concludes that procedural reform, clearer legal limitations on the authority of proposing institutions, and stronger judicial ethics oversight are essential to restoring the Constitutional Court’s independence. By highlighting the structural dimensions of political intervention, this article contributes to the broader scholarly discourse on judicial independence and constitutional adjudication in democratic systems.